Democratic distributive justice - Zucker, Ross, 1952- (Cambridge University Press, 2001)
"By exploring the integral relationship between democracy and economic justice, Democratic Distributive Justice seeks to explain how democratic countries with market systems should deal with the problem of high levels of income inequality. The book acts as a guide for dealing with this issue by providing an interdisciplinary approach that combines political, economic, and legal theory. The book also analyzes the nature of economic society and puts forth a new understanding of the agents and considerations bearing upon the ethics of relative pay, such as the nature of individual contributions and the extent of community in capital-based market systems